Two-phase orthodontic treatment using the segmented edgewise technique for ectopic canine correction: a case report - Komang Abhigamika Wijayadharma; Lina Lestia; Christnawati; Ananto Ali Alhasyimi; Francisco José Vázquez-Santos (Dental Journal (Majalah Kedokteran Gigi), 2026)
Background: Ectopically erupting canines are a common challenge in orthodontic practice, often occurring as a result of insufficient dental arch space. Failure to manage ectopic eruptions can lead to arch length loss and malocclusion. The main advantage of two-phase treatment using segmental loop mechanics is the absence of friction between the bracket and archwire during space closure, making it an efficient way to achieve canine retraction and minimizing loss of anchorage and anterior flaring. Purpose: To describe the effectiveness of using a two-phase orthodontic edgewise prescription without any side effects. Case: A 21-year-old female patient presented with a primary concern of crowding and misaligned canines. A dentoskeletal Class I relationship, lower dental midline shifted 4.15 mm to the right, 4.4 mm overjet, 3 mm overbite, and mesiobuccally ectopic #23 and #43 were detected. Case Management: Four premolars were extracted (#15, #24, #34, #44); segmented edgewise brackets with a 0.022” slot and 0.014” stainless steel archwires, complete with a vertical loop and helix, were installed and activated to retract #13 and #43 until they were aligned and leveled. The treatment proceeded with insertion of the remaining brackets, followed by leveling and alignment, canine retraction, posterior mesialization, and space closure. Treatment results showed correction of the ectopic canine position with a Class I relationship, overjet reduced to 2.3 mm, overbite reduced to 2 mm, and midline deviation reduced to 1.30 mm to the right. Conclusion: The two-phase orthodontic treatment using the segmental technique with edgewise prescription effectively corrected the ectopically erupting canines without revealing any side effects.